10Be content in clasts from fallout suevitic breccia in drill cores from the Bosumtwi impact crater, Ghana: Clues to preimpact target distribution. (3rd February 2014) - Losiak, Anna; Wild, Eva Maria; Michlmayr, Leonard; Koeberl, Christian
Abstract Rocks from drill cores LB‐07A (crater fill) and LB‐08A (central uplift) into the Bosumtwi impact crater, Ghana, were analyzed for the presence of the cosmogenic radionuclide 10Be. The aim of the study was to determine the extent to which target rocks of various depths were mixed during the formation of the crater‐filling breccia, and also to detect meteoric water infiltration within the impactite layer. 10Be abundances above background were found in two (out of 24) samples from the LB‐07A core, and in none of five samples from the LB‐08A core. After excluding other possible explanations for an elevated 10Be signal, we conclude that it is most probably due to a preimpact origin of those clasts from target rocks close to the surface. Our results suggest that in‐crater breccias were well mixed during the impact cratering process. In addition, the lack of a 10Be signal within the rocks located very close to the lake sediment–impactite boundary suggests that infiltration of meteoric water below the postimpact crater floor was limited. This may suggest that the infiltration of the meteoric water within the crater takes place not through the aerial pore‐space, but rather through a localized system of fractures.